Irrational Beliefs and Academic Dishonesty: The Mediating Role of Catastrophising in a REBT-Based Model - Salsabila Yuli Adys Hermawan; Diniy Hidayatur Rahman; Devy Probowati (Cakrawala Bimbingan dan Konseling, 2026)
Academic dishonesty is a significant issue that threatens the integrity of education. Previous studies indicate that internal psychological factors, particularly irrational beliefs, may influence students’ tendencies to engage in such behavior. Based on the framework of Rational Emotive Behavior Therapy (REBT), this study examines the relationships between demandingness (as a primary irrational belief) and catastrophising, self-depreciation, and low frustration tolerance (as secondary irrational beliefs) with academic dishonesty. This research employed a quantitative correlational design involving 104 students of SMAN 1 Maospati selected through stratified random sampling. Data were collected using the Attitudes and Beliefs Scale II (ABS-II) and an Academic Dishonesty scale, and were analyzed using path analysis. The results indicate that demandingness is significantly related to catastrophising, and catastrophising is significantly associated with academic dishonesty. In contrast, self-depreciation and low frustration tolerance show no significant relationships with academic dishonesty. These findings suggest that catastrophising acts as a cognitive mechanism linking irrational demands to the tendency to engage in academic dishonesty. The study highlights the importance of REBT-based counseling interventions to help students modify catastrophic thinking patterns and prevent academic dishonesty.